2016
DOI: 10.1038/onc.2016.417
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase promotes stem cell phenotype in triple-negative breast cancer through upregulation of Notch1 via activation of c-Jun

Abstract: c-Jun N-terminal kinase (JNK) plays a vital role in malignant transformation of different cancers, and JNK is highly activated in basal-like triple-negative breast cancer (TNBC). However, the roles of JNK in regulating cancer stem-like cell (CSC) phenotype and tumorigenesis in TNBC are not well defined. JNK is known to mediate many cellular events via activating c-Jun. Here, we found that JNK regulated c-Jun activation in TNBC cells and that JNK activation correlated with c-Jun activation in TNBC tumors. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 45 publications
3
75
0
Order By: Relevance
“…The observation that the AP1 family protein c‐Jun activates Notch1 transcription has recently been made in triple‐negative breast cancer cell lines , therefore, consistent with our data. In similar experiments as ours, Xie et al.…”
Section: Discussionsupporting
confidence: 92%
“…The observation that the AP1 family protein c‐Jun activates Notch1 transcription has recently been made in triple‐negative breast cancer cell lines , therefore, consistent with our data. In similar experiments as ours, Xie et al.…”
Section: Discussionsupporting
confidence: 92%
“…Because the enrichment of c-Jun and Fos activity was detected in the hepatoblast subtype of HCC arising from bipotential HPCs, this indicated that the AP-1 complex was the major driving force in tumorigenesis of the hepatoblast subtype [3]. Moreover, positive feedback regulation of OCT4 and c-Jun, resulting in the continuous expression of c-Jun, was critical for the induction of CSC-like characteristics in liver cancer [49], as seen in other cancers [50,51]. These results illustrate that the activation of c-Jun in HPCs is responsible for their malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…As activated JNK moves into the nucleus, JNK catalyzes the phosphorylation of a protein substrate by forming a ternary complex with its downstream substrate and transferring the γ-phosphate of ATP. JNK predominately phosphorylates the N-terminal Ser63 and Ser73 residues of c-Jun, a member of activator protein 1 (AP-1) transcription factor family, thus enhancing its transcriptional activity [26,27]. Other downstream substrates of JNK are transcription factors, including members of the activating transcription factor (ATF) family, c-Myc, p53, nuclear factor of activated T-cells-4 (NFAT4), and Elk-1 and non-transcription factors, including the Bcl-2 family [28][29][30][31].…”
Section: The C-jun N-terminal Kinase (Jnk) Pathwaymentioning
confidence: 99%